RANCANG BANGUN MODUL PRAKTIKUM SISTEM EMBEDDED BERBASIS RASPBERRY PI (MODUL 2: PENERAPAN SISTEM SEDERHANA) - I Putu Pawesi Siantika; Pratolo Rahardjo; I Gusti Agung Putu Raka Agung (Jurnal SPEKTRUM, 2021)
Embedded systems play a very important role in various fields so that several universities,especially Udayana University in the Electrical Engineering Study Program, Faculty ofEngineering have included embedded systems + lab courses. However, the availability ofsupporting facilities for activities in the lab is not yet available as it should be. Based on this, inthis research, a practicum module for an embedded system based on Raspberry Pi will bedesigned and made (Module 2: implementation of a simple system). This practicum module hasthree experiments, namely a lamp control system and a 5 V DC motor equipped with an LDRsensor (experiment 1); monitoring the water level using the HC-SR04 sensor module and theheight data is displayed on a 16 x 2 LCD (experiment 2); Human movement detection uses theHC-SR501 sensor module with output in the form of audio that is channeled to the speaker, theimage display by the 0.96 inch OLED module, and the rotation of the LDR servo shaft(experiment 3). The results obtained in the three experiments are that all systems worksuccessfully with the following conditions: The load on the relay turns on when the LDR sensorcondition is covered with black cloth, the load on the relay goes out when the LDR sensorcondition is left unobstructed and the LDR sensor is illuminated by an LED flashlight. The LEDindicator lights up according to the condition of the water level reading by the HC-SR04 sensormodule. The HC-SR501 sensor module successfully detects the movement of objects in theform of humans at a distance of 1 m, 1.5 m, and 3 m.